Facilities management education in the Four Asian Dragons: a review. Issue 11 (5th August 2019) - Lai, Joseph; Tu, Kung-Jen; Lian, Jonathan K.M.; Kim, Jun Ha
Abstract : Purpose: This paper aims to reveal and compare the characteristics of the facilities management (FM) education programs in Hong Kong, Taiwan, Singapore and South Korea (i.e. the Four Asian Dragons) and makes suggestions for their future development. Design/methodology/approach: A team consisting of academics from the Four Asian Dragons held a face-to-face meeting to discuss and define the scope and framework of the review, followed by an extensive search to identify literature and information germane to the study. Individual parts of reviews, prepared by the team members for their respective places, were cross-reviewed before refinement and consolidation into the current paper. Findings: The term "facility (or facilities) management" appears in most of the programs reviewed, but terms such as "environment" and "property" also appear in some programs' titles. The programs reviewed range from certificate level to doctorate level; those between diploma level and master level are more common. Most of the programs have obtained professional accreditations, but some are accredited by FM-related rather than FM-specific professional bodies. Research limitations/implications: Further research should investigate issues such as the performance of the programs reviewed, extent to which they have met the market needs and how they compare with the counterparts in other regions (e.g. Europe, America). For such research, the process of the study reported here and its findings about the status quo of the programs can serve as references. Practical implications: To strengthen FM as a well-established discipline, it is imperative to have the programs accredited by FM-specific professional bodies. Originality/value: Providing the first-ever international review on the major FM programs in Asia, this paper is useful to program planners, educators and researchers in the FM field.